Perbandingan Pemeriksaan Skrining Antibodi (Indirect Coombs Test) dengan Direct Coombs Test pada Pasien dengan Riwayat Transfusi Darah Berulang - Arta, Shela Yuni; Suhariyadi, Suhariyadi; Woelansari, Evy Diah; Rahayuningsih, Christ Kartika (Jaringan Laboratorium Medis, 2025)
Repeated blood transfusions can increase risk of alloimmunization and autoimunization, which causes formation alloantibodies and autoantibodies. The presence of these antibodies can make cross-matching more difficult and increase the possibility of hemolytic transfusion risk. Antibody screening tests (Indirect Coombs Test) and Direct Coombs Test play a role in detecting the presence of alloantibodies and autoantibodies in patient with a history of repeated transfusion. The aim of the study was to determine the diferences in results between antibody screening (Indirect Coombs Test) and Direct Coombs Test in patients receiving repeated blood transfusions. This study used a quasi-experimental design with a cross-sectional approach. The subjects were patients with a history of blood transfusions more than 5 times at RSUD R.T. Notopuro Sidoarjo totalling 60 samples. The data obtained were then analyzed statistically to see if there were any significant differences between the two types of examinations. The results obtained showed a significant difference between the results of the antibody screening test (ICT) and the Direct Coombs Test (DCT) (p-value 0.000), that more patients with repeated blood transfusions had positive DCT results (75%). Some patients showed positive results on one or both types of tests, indicating the presence of alloantibodies or autoantibodies. ICT and DCT tests provide complementary information in detecting antibodies in patients with repeated transfusions. The use of both is important in improving the safety of blood transfusions and minimizing the risk of hemolytic reactions.